Theosophy across boundaries: transcultural and interdisciplinary perspectives on a modern esoteric movement - Strube, Julian; Krämer, Hans Martin (SUNY Series in Western Esoteric Traditions, 2020)
"Demonstrates that Theosophy was part of a truly global movement and played an important role in the general histories of religion, science, philosophy, art, and politics"--